PSVI-30 Logistic regression analysis of the related factors in discarded semen of boars in Southern China. (7th December 2018) - Chao, W; Liang, G; Qing, S; Peng, J
Abstract: This study aimed to investigate the factors affecting the discarded semen of boars. A total of 176, 368 ejaculates of boars from 9 AI centers were collected from January 2013 to May 2016 in Southern China. A logistic regression model was used to analyze the effects of housing type, breed, boar age, season, and age at herd entry on discarded semen of boars. The proportion of the discarded semen (PDS) was 13.09%. Chi-square test showed semen discarded due to plasma drops had the greatest PDS among all reasons (31.60%), followed by impurity (25.96%), sperm agglutination (20.31%), coiling tail (17.72%), low concentration (10.86%), and others (6.78%; P < 0.0001). Furthermore, logistic regression results revealed PDS was affected by all of these 5 factors (P < 0.0001). Boars raised individually in stalls exhibited greater PDS than those raised individually in pens (OR = 1.657; 95% CI 1.607 – 1.709). Duroc (OR = 1.130; 95% CI 1.093 – 1.167) and Yorkshire boars (OR = 1.432; 95% CI 1.380 – 1.486) both had greater PDS than Landrace boars. The PDS of adult boars (aged 13 to 24 mo, 25 to 36 mo, and more than 37 mo: OR = 0.800, 0.941, and 0.838, respectively; 95% CI = 0.771 – 0.831, 0.902 – 0.983, 0.790 – 0.889, respectively) were lower than that of young boars (aged less than 12 mo). Boars aged 5 to 7 mo (OR = 1.432; 95% CI 1.380 – 1.486) and aged 10 to 12 mo (OR = 1.432; 95% CI 1.380 – 1.486) at herd entry had greater PDS than those aged 8 and 9 mo. In conclusion, the PDS is affected by housing type, breed, boar age, season, and age at herd entry. Importantly, 8 and 9 mo are suggested as the most suitable age for boar introduction.